Application of a Single-Phase Matrix Converter for Electric Vehicle Charging - Diaz-Diaz, M; Vidal-Nunez, C (Institute of Electrical and Electronics Engineers Inc., 2022)
The Single-Phase Matrix Converter has been identified as a potential alternative to enable bidirectional residential electric vehicle charge due to its direct AC-AC conversion, high power density, and bidirectional power flow. However, implementation issues for single-phase circuits, such as providing a path for inductive currents and the development of modulation techniques for isolated operation, should be addressed. Consequently, this paper describes the design and modulation voltage of a Single-Phase Matrix Converter for electric vehicle charger applications. A modulation strategy is proposed based on four step commutation. Simulation results obtained using an RTBox real-time simulator are presented to validate the effectiveness of the Single-Phase Matrix Converter for electric vehicle charging. © 2022 IEEE.